Evaluasi Pengelolaan Dana Desa di Desa Putren Kecamatan Sukomoro Kabupaten Nganjuk - Gagarin Putra; Pratiwi Dwi Karjati (Economie: Jurnal Ilmu Ekonomi, 2019)
Improving the welfare of the people who live in residential areas / hated, the government embodies the Village Fund which encourages the development of the Village to provide funding from the National Budget. However, at the moment, there is still a lack of understanding of the Village officials on the administration and accountability of Village fund users which is a problem in effective and efficient village fund management. This study was designed to describe the evaluation of village fund management in Putren Village, Sukomoro District, Nganjuk Regency. This research is a qualitative descriptive analysis. Data used is sourced from primary data obtained by conducting interviews with several informants and making observations. The instruments used in this study were interview guides and observation sheets. The data analysis technique used is qualitative analysis with interactive models. The results in this study indicate that: (1) several activities have been realized such as road repairs with the construction of paving, repair of culverts; (2) HR in managing village funds meets the requirements, but in terms of quality guidance is still needed; (3) village funds have not been optimal in helping economic problems because they require infrastructure development assistance; (4) distribution of village funds has been evenly distributed and evenly distributed by prioritizing villages in need; (5) the community is very enthusiastic in participating in the management of village funds specifically in assisting the implementation of infrastructure development; (6) village funds that are channeled are very beneficial and beneficial to the community for infrastructure development.